TOTAL KAROTENOID IKAN SUMATRA ALBINO (Puntius tetrazona) YANG DIBERI PAKAN TAMBAHAN TEPUNG KEPALA UDANG - Tania, Novita; Sukarman, Sukarman; Permana, Asep; Supiyani, Atin (LPPM Universitas Negeri Jakarta, 2018)
ABSTRACTAlbino tiger barb (Puntius tetrazona) is a freshwater ornamental fish that has a attractive colors. Carotenoid sources should be added in the diet because fish can not synthesis carotenoids in their bodies. One source of natural carotenoids (astaxantin and cantaxantin) is shrimp head meal, whose use has not been studied in albino tiger barb (Puntius tetrazona). The research was conducted from December 2016 until April 2017, at the Balai Riset Budidaya Ikan Hias (BRBIH) Depok. The method used in this research is an experimental method, with Completely Randomized Design (RAL). The treatment in this research is TKU supplemental feeding (0%, 10%, 20%, 30%, 40%). The data taken are total carotenoid, were analyzed using One Way ANAVA at 95% confidence level and continued with Duncan test at Î± <0,05 with SPSS 17.0 program. The result of the research is the addition of the best TKU by 30% to improve the color quality, total carotenoids, and growth of albino tiger barb (Puntius tetrazona). The highest increase in total carotenoids at the fins of 13.54 Â± 0.24 ppm and on the skin was 7.54 Â± 0.11 ppm. Keyword: Shrimp Head Meal, Carotenoid, Feed, Color Quality, Puntius tetrazona.